GRAPHIC DESIGN IN CLOTHING FABRIC AS A PART OF AN IMAGE DESIGN - Ignatovica, Agate; Apele, Diana (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2016)
The aim of the article is to explore the psychological effects that clothing fabric patterns leave on personal image, as well as to understand graphical forms with whom we can help to create the body optical illusions. Research methods: Theoretical – the appropriate literature, scientific database and internet source research. Lecture visits of professional image designers and stylists, interviews and personal experience in this sphere.Conclusion: Any type of textile print will leave an effect and create associations. Form and colours create the textile print. By choosing the right type of print, the wearer can create a certain psychological mood, as well as optically correct the parts of the body. When choosing a textile print, several factors must be taken in notice – body type, silhouette type, colours of the season, age, social status, individual style etc. If faced with contradictory information about the style, priority should be given to own personal reference, because that will create a harmonious essence as well as create a psychological comfort to the wearer.